FACTORS RELATED TO EARLY MARRIAGE AT STATE HIGH SCHOOL 1 MENTOK IN 2024 - Sulastri, Yeni; Siswanto, Siswanto; Murniani, Murniani (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Early marriage is a marriage between young couples under the age of 20, namely women <18 years old and men <20 years old. Early marriage is a phenomenon that often occurs in Indonesia. To prevent the further increase and increase of early childhood marriage, the cooperation of various parties, both the government, the private sector, and the community, is needed which aims to increase knowledge and prevent further increase in early childhood marriage at SMA Negeri 1 Mentok, West Bangka Regency. This study aims to find out the factors of the role of peers and the role of mass media with knowledge about early marriage at SMA Negeri 1 Mentok, West Bangka Regency. This study uses a quantitative descriptive method with a cross sectional design. The population of this study is 573 male and female students of grades XI and XII of SMA Negeri 1 Mentok, West Bangka Regency, sampling using random sampling technique with a sample of 94 students. Data analysis was carried out using univariate, bivariate analysis and Chi-Square test. The results showed that there was a meaningful relationship between the role of peers and early marriage knowledge in, with a p-value of 0.017 < α (0.05) for both variables, the relationship between the role of mass media and early marriage knowledge was obtained with a P value of (0.404) > α (0.05), meaning that Ho was accepted, there was no meaningful relationship between the role of mass media and early marriage knowledge. The role of peers is related to early marriage knowledge, while the role of mass media is not related to early marriage knowledge in the SMA Negeri 1 Mentok area, West Bangka Regency in 2024.